Prevalence of nutritional deficiencies other than anaemia among students of government commerce college of Gandhinagar, Gujarat: a cross sectional study - Jain, Uresh Jayantilal; Shah, Varsha; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2016)
Background: Adolescence and young adulthood are periods of critical development and transition. Adolescent constitutes over 23% of the population in India. Nutrition and health needs of the adolescent are more because of more requirements for growth spurt and increase in physical activity. The aim was to study prevalence of nutritional deficiencies other than anaemia among students of Government Commerce College. Methods: The study was carried by Medicine Department, GMERS Medical College, Gandhinagar, India during period from July 2016 to August 2016 in purposively selected government college of Gandhinagar city. After taking the permission of principal of college and consent of the students, 421 students were examined for signs of various nutritional deficiencies other than anaemia. The data was collected by predesigned, pretested proforma and analyzed using SPSS 17.0 (Trial Version). Results: Out of total 421 students 205 (48.6%) were female. Mean age of the study students was 19.8±1.66 years. Maximum numbers of the students were in the age group of 18-21 years (60.5%). Mean age of female and male students was 19.7±1.79 years and 19.9±2.01 years respectively. The study revealed that vitamin A deficiency was present in 28 (7.0%) students. Vitamin B complex deficiency signs were seen in 96 (23.1%) students. Vitamin C deficiency signs were seen in 44 (10.5%) students. PEM was observed in 55 (13.2%) students. Essential fatty acid deficiency was observed in 60 (14.4%) students. Conclusions: High prevalence of nutritional deficiencies among these students needs great attention and health education.